Physical, functional and sensory properties of bitter chocolates with incorporation of high nutritional value flours - Quispe-Sanchez, Luz; Mestanza, Marilu; Goñas, Malluri; Gill, Elizabeth Renee Ambler; Oliva-Cruz, Manuel; Chavez, Segundo G. (Frontiers in Nutrition, 2022)
Due to the growing demand for healthy food products, the industry is seeking to incorporate inputs with high nutritional potential to traditional products. The objective of this research was to evaluate the effect of incorporating Lepidium meyenii, Chenopodium pallidicaule, Amaranthus caudatus, Sesamum indicum and Salvia hispanica flours on the physical, chemical, rheological, textural and thermal characteristics, and the degree of sensory acceptance of dark chocolate bars (65% cocoa). To this end, chocolate bars were made with the incorporation of five flours in four doses (1, 2, 3 and 4 %), obtaining 20 different formulations compared with a control treatment (without flour addition). It was found that, as flour incorporation levels increased, viscosity, antioxidants and particle size of the chocolates increased, but hardness and pH decreased. The addition of the flours also affected the acceptability and microstructure of the chocolate bars. Consequently, the incorporation of grain flours with high nutritional value can enhance the characteristics of dark chocolates, becoming a technological alternative for the chocolate industry.